ANALISIS TINGKAT KEPUASAN PETUGAS REKAM MEDIS ELEKTRONIK DENGAN PENDEKATAN END-USER COMPUTING SATISFACTION - Zhenya, Zhenya Zeldha Elyzvania; Irwandi, Irwandi; Adha Taufik, Anvika; Sinaga, Rudolf (Journal of Hospital Administration and Management (JHAM), 2025)
The implementation of electronic recording systems like Electronic Medical Records (EMR) is expected to ease and accelerate service provision. However, EMR applications don't always fully support healthcare professionals in their duties. Therefore, an evaluation is crucial to identify system weaknesses. User satisfaction with electronic medical records is a key indicator of information system success. This study aimed to determine the satisfaction level of electronic medical record officers using the End-User Computing Satisfaction (EUCS) method, based on the dimensions of Content, Accuracy, Format, Ease of Use, and Timeliness. This descriptive quantitative study used a survey method, distributing questionnaires to 39 EMR user officers. Data analysis involved descriptive statistics and hypothesis testing using multiple linear regression. The results showed all variables were in the very satisfied category, with average values of Content 4.33, Accuracy 4.31, Format 4.35, Ease of Use 4.23, and Timeliness 4.27. The F-test also indicated that all five EUCS variables simultaneously had a significant effect on user satisfaction. Thus, it can be concluded that the EMR system at UPTD Koni Health Center has met end-user expectations regarding its operations. UPTD Koni Health Center is advised to continuously improve the quality of the EMR system, conduct ongoing evaluations and improvements in areas with a medium satisfaction level, and strategically plan EMR system development to support more efficient health services.